Effects of the Nurse Competency Improvement Program in Caring for Pediatric Patients with Cardiac Arrhythmia on Knowledge, Attitude, and Caring Skills for the Pediatric Patients with Cardiac Arrhythmia - Theannamngian, Onchira; Kanchanabutr, Phavinee; Kasemsook, Chirawachr (Journal of Thailand Nursing and Midwifery Council, 2025)
Introduction Cardiac arrhythmia in pediatric patients is a medical emergency that can be life-threatening, particularly among children with congenital heart disease. Nurses who care for pediatric patients with this condition need specialized competencies to help reduce complications and mortality rates. Currently, Thailand Nursing and Midwifery Council is no established framework outlining the specific nursing competencies required for managing pediatric arrhythmias. Moreover, despite having received advanced pediatric life support training, many nurses still lack the necessary skills to effectively care for children experiencing arrhythmic episodes. Therefore, the development of an educational program aimed at enhancing nurses’ competencies in managing pediatric arrhythmias represents a critical strategy to improve the quality of care for this vulnerable patient population. Nurses who care for pediatric patients with this condition need specialized competencies to help reduce complications and mortality. Currently, it is found that there are no specialized nursing competency requirements to care for pediatric patients with arrhythmias. It was found that nurses have limited skills in caring for pediatric patients when arrhythmias occur, even though they have been trained in pediatric advanced life support. Therefore, the development of teaching programs to improve nurses’ competency in caring for children with arrhythmias is one of the approaches to promote the competence of nurses in caring for this group of patients. Objective To investigate the effects of the nurse competency improvement program in caring for pediatric patients with cardiac arrhythmias by comparing the knowledge, skills, and attitudes of nurses towards caring for children with arrhythmias between before and after participating in the program. Design This study employed a quasi-experimental, one-group pretest-posttest design, applying the coaching framework proposed by Helfer and Willson into the instructional process of a competency development program for nurses caring for pediatric patients with cardiac arrhythmias. The coaching process consisted of four key stages: 1) establishing rapport and providing information, 2) skill development through instruction and hands-on practice, 3) skill reinforcement through review, and 4) follow-up and evaluation. The program aimed to enhance nurses’ competencies in managing pediatric arrhythmias, including nine core competencies: 1) performing 12-lead electrocardiograms, 2) interpreting ECG results, 3) nursing care for pediatric patients with bradyarrhythmias, 4) nursing care for pediatric patients with tachyarrhythmias, 5) administration of anti-arrhythmic medications, 6) performing vagal maneuvers, 7) caring for patients undergoing cardioversion or defibrillation, 8) managing patients with temporary pacemakers, and 9) providing care for pediatric patients experiencing cardiac arrest. Learning outcomes were assessed based on Bloom’s taxonomy, including cognitive, affective, and psychomotor domains, resulting in improved knowledge, clinical skills, and attitudes toward nursing care for pediatric patients with cardiac arrhythmias. Methodology The study participants consisted of 12 newly graduated nurses working in the pediatric cardiology unit at a tertiary-level hospital in Bangkok. Participants were purposively selected based on the following inclusion criteria: 1) holding a Bachelor of Nursing Science degree in Nursing and Midwifery, 2) having 1–5 years of clinical nursing experience, 3) being proficient in computer use and owning a smartphone capable of using the LINE application, and 4) voluntarily agreeing to participate in the program. The sample size was determined using power analysis via the G*Power software. The research instruments were divided into two components: 1) the competency development program for nurses caring for pediatric patients with cardiac arrhythmias, which included theoretical and practical teaching plans, a training manual, Powerpoint presentations, instructional videos, LINE application content, medical equipment and medications, and pediatric advanced life support trainer with arrhythmia simulation, and 2) data collection tools, consisting of a demographic information questionnaire, a knowledge assessment tool for pediatric arrhythmia care, a skill assessments in caring for pediatric patients with arrhythmias, and a questionnaire assessing nurses’ attitudes toward developing competencies in pediatric arrhythmia care. Data collection was conducted from June to July 2024 and analyzed using descriptive statistics and Paired t-tests. Results The majority of participants had prior experience in caring for pediatric patients with cardiac arrhythmias (75%). Additionally, 91.7% reported that their workplace provided opportunities to care for such patients. Half of the participants (50%) had received training on electrocardiogram (ECG) interpretation at least once, and an equal proportion had undergone training specifically focused on ECG interpretation in pediatric patients. Furthermore, 58.3% had received training in pediatric arrhythmia care, while 91.7% had completed advanced pediatric life support training. Analysis of the overall knowledge revealed that knowledge after the program (M = 66.75, SD = 14.81) was higher than before the program (M = 25.75, SD = 10.81; t = 11.660, p < .001). Similarly, the mean skill in pediatric arrhythmia care after the program (M = 55.67, SD = 5.16) was significantly higher than before the program (M = 6.25, SD = 3.70; t = 33.754, p < .001). However, the mean attitude before (M = 25.83, SD = 2.44) and after the program (M = 26.08, SD = 4.64) were not statistically different (t = .248, p = .405). Recommendation Healthcare institutions responsible for the care of pediatric patients with cardiac arrhythmia can consider adopting this program as part of nurse training initiatives. The program has the potential to enhance nurses’ competencies, particularly knowledge and skills related to the care of children with arrhythmias. Future studies should employ an experimental research design to validate the findings and assess long-term outcomes.